Hydro‐Functional Traits and Their Dissimilarity to the Neighbourhood Buffer Tree Growth Against the 2018–2020 Central European Drought - Lena Sachsenmaier; Florian Schnabel; Fon R. Tezeh; Pablo Castro Sánchez‐Bermejo; Nico Eisenhauer; Olga Ferlian; Sylvia Haider; Ronny Richter; Sharath S. Paligi; Bernhard Schuldt; Christian Wirth (Global Change Biology, 2025)
Climate change is predicted to increase the frequency and duration of drought events, threatening the functioning of Central European forests. While diverse forests often promote long‐term growth stability, their performance during extreme drought events remains debated. Understanding the effects of forest diversity on tree growth during drought requires not only a consideration of tree interactions with direct neighbouring trees but also of the species' morphological and physiological characteristics, i.e., a trait‐based approach. Contrasting species‐specific drought responses might be driven by hydro‐functional traits, which shape a tree's hydraulic safety and stomatal control strategy. We investigated individual tree growth before, during, and after the unprecedented 2018–2020 Central European drought, from a hydro‐functional perspective. We analysed annual growth data from 2611 trees in a temperate tree diversity experiment (MyDiv experiment, Germany), measured 14 hydro‐functional traits, and modelled individual tree growth across the years 2016–2021, considering the interaction of climatic conditions with hydro‐functional trait syndromes. Our results reveal that traits related to hydraulic safety and stomatal control potential were key drivers of tree growth across drought and non‐drought years. During the severe multi‐year drought, the growth of focal trees increased with either higher hydraulic safety or tighter stomatal control potential. Trait syndromes that were less advantageous under normal conditions provided beneficial effects under drought stress, reflecting a trade‐off in performance across conditions. Additionally, we found that hydro‐functional dissimilarity between a tree and its surrounding neighbors provided benefits for tree growth during drought. Therefore, our study suggests that planting tree mixtures with distinct hydro‐functional strategies can enhance resistance to future droughts.